External return-to-work programs impact on women relauching their careers - Frisch, K.; Costa, S.; Matos, F. (Proceedings of the 7th International Conference on Gender Research, 2024)
Women have higher drop-out rates during their professional careers, mainly due to family, child, or elderly care; furthermore, they have more difficulty returning to the workforce even if they are highly qualified, making the future of gender equality in the workplace a continuing challenge. Thus, encouraging women to re-enter the workforce after a career break makes sense from a gender perspective and, at the same time, can also add value to the economy by providing qualified and diversified resources to companies (large ones or small-medium-sized enterprises, or SMEs). Additionally, this encouragement can have short- to medium-term positive effects on career-break women who would like to return to the workforce, as well as long-term effects due to lower or no pension contributions during their career break. The aim of this study is to identify the push and pull factors affecting women´s ability to return to the job market after a career break. Moreover, the purpose of this study is to understand what has been studied about the impact of return-to-work/returnship programs (RTW) and externally provided return-to-work programs (RTWE) in helping bring back women to the labor market. The research is qualitative and exploratory, based on a literature review. The findings of this research provide an overview of relevant factors related to women’s return to the market and allow for new research avenues on RTWE’s outcomes for both women and small and medium-sized enterprises. In terms of originality, the goal of this research is to encourage data-driven debates about the potential implications of women's return-to-work programs as a strategy to help women return to the workforce and whether this strategy can be adopted by different-sized companies.